POSACONAZOLE - NEW AZOLE BROAD-SPECTRUM ANTIFUNGAL AGENT FOR PREVENTION AND TREATMENT OF INVASIVE MYCOSES - N.N. Klimko ("Paediatrician" Publishers LLC, 2008)
Invasive mycoses are a common complication of various categories of immune depressed patients that are characterized with heavy clinical presentations and high lethal rate. Many causatives of invasive mycoses are resistant to currently applied antifungal medications, and some are polybresistant. Posaconazole (Noksafil) is a new triazole antimycotic of second generation that is active both in vitro and in vivo against most causatives of invasive mycoses, including poly resistant microbmycets. Clinical study demonstrate high efficiency and safety of applying this medication. in russia posaconazole is allowed for prevention of invasive mycoses for hematological patients with longbrunning neutropenia resulting from chemical therapy, who are prescribed large doses of immune suppressors, recipients of transplants of hemapoietic stem cells, as well as for treatment of invasive candidoses, aspergillus, zigomicosys, criptococcosis, fuzariosis, chromomycosis and micetoma, as well as cocsidiodosis that are refractory towards other anti fungal medications, or in cases of intolerance. Key words: mycoses, posaconazole, treatment.